Effect of light-curing unit and bonding agent on shear bond strength of composite resin to dentin - Parvin Mirzakouchaki borojeni; Mehrdad Barekatain; Banafsheh Padidar (Isfahan University of Medical Sciences, 2011)
Introduction: Shear bond strength is one of the most important mechanical characteristics involved in clinical durability of tooth-colored restorations, which is directly related to polymerization shrinkage. This study evaluated the efficacy of two light-curing units (LED2 & QTH) and two types of dentin bonding agents (Excite & Clearfil SE bond) on composite resin shear bond strength to dentin.Materials and Methods: Forty caries-free sound human premolars were randomly divided into 4 groups of 10 after being disinfected with sodium hypochlorite. The occlusal surface of dentin in each specimen was exposed and flattened by a fissure bur; composite resin was bonded with Excite or Clearfil SE bonding agents and polymerized with QTH or LED2. Shear bond strength values of the specimens were tested in a Dartec universal testing machine. Data were analyzed by one-way ANOVA, two-way ANOVA and Dunkan test (α = 0.05).Results: Maximum shear bond strength values were recorded in composite restorations bonded with Clearfil SE bonding agent and polymerized by LED2; minimum values were recorded in composites restorations bonded with Excite and polymerized by QTH. Statistical analysis showed statistically significant differences between the experimental groups (p value = 0.03).Conclusion: Under the limitations of this study, it can be concluded that two curing systems of LED2 & QTH are equally effective on shear bond strength of different bonding agents, whereas Clearfil SE bonding agent produces higher shear bond strength than Excite total-etch regardless of the type of light-curing unit. Key words: Light curing, Bonding agent, Bond strength, Composite resin.